Association of ovarian volume with insulin resistance in PCOS patients - Ahmed, Naorin; Akhter, Dilruba; Eva, Nusrat Jahan; Khan, Ahsan Habib; Nesa, M. Karimatun; Nahar, M. Irin; Haider, Chowdhury Afsana; Ripa, Halima Jahan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women, characterized by hyperandrogenism, menstrual irregularities, polycystic ovarian morphology, and often associated with insulin resistance. The purpose of this study was to assess the association between insulin resistance and ovarian volume in PCOS patients, comparing women with ovarian volume >10 cc to those with ≤10 cc. The aim of the study was to evaluate the association between ovarian volume and insulin resistance among patients diagnosed with polycystic ovary syndrome (PCOS). Methods: This comparative cross-sectional study at the department of obstetrics and gynecology, ICMH, Dhaka (October 2022-September 2023) included 66 women with PCOS (18-35 years), divided by ovarian volume into Group A (>10 cc, n=34) and Group B (≤10 cc, n=32). Fasting glucose, insulin, HOMA-IR, hirsutism, BMI, and waist-to-hip ratio were assessed, analyzed with SPSS v27 (p<0.05). Results: In 66 PCOS patients, groups were similar in age, BMI, waist-to-hip ratio, menarche, parity, and Ferriman-Gallwey score (all p>0.05); HOMA-IR was higher in group A (4.83 versus 3.59; p=0.012), correlated with ovarian volume (r=0.685, p<0.001), and HOMA-IR ≥3.8 increased odds of ovarian volume >10 cc (67.6% versus 21.9%; OR=7.468; 95% CI=2.476-22.522; p<0.001). Conclusions: Higher insulin resistance (HOMA-IR ≥3.8) is significantly associated with larger ovarian volume (>10 cc) in PCOS patients, suggesting ovarian volume as a potential indicator of insulin resistance.